SOSIALISASI PROBLEMATIKA PERTANAHAN DAN STRATEGI PENYELESAINNYA BAGI MASYARAKAT DESA NGAYUNG - Arezqi Tunggal Asmana; Anis Lailiyatur Rohmah; Mufidatul Ummah; Markub Markub; Moh. Azus Shony Azar (LPPM Universitas Islam Darul 'Ulum Lamongan, 2021)
Land in society has a close relationship with one's prosperity. This can be seen from the number of land disputes that have long been a social reality in society. The issue of land law is a problem that is often faced by the people of Indonesia, including the people in Ngayung Village, Maduran District, Lamongan Regency. The process of proving land ownership which will go through the issuance of land certificates is an important thing to strive for in order to minimize the emergence of a land dispute problem. Therefore, the Lecture Group (KKN) team has collaborate with several communities held consultations on land law issues and how to solve them for the community. By inviting legal consultants who aim to explain various kinds of problems and open up opportunities for assistance for Ngayung Village residents who are facing problems related to land law and its structure.